Highly Stretchable Polymer Transistors Consisting Entirely of Stretchable Device Components. (24th March 2014) - Shin, Minkwan; Song, Jun Hyuk; Lim, Guh‐Hwan; Lim, Byungkwon; Park, Jong‐Jin; Jeong, Unyong
<x xml:space="preserve">Abstract</x> Wrinkle‐free stretchable organic transistors are fabricated using stretchable device components (substrate, electrodes, dielectric, active layer). The stretchable device showed no degradation during repeated cycles of stretching at ε = 0.7. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>